Active material for secondary battery electrodes and secondary battery using same
By controlling the carbon layer thickness ratio on olivine-type secondary battery electrodes, the material achieves improved electronic and ionic conductivity, addressing the limitations of random thickness variations and enhancing battery performance.
Patent Information
- Application Number
- JP2020568571
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-27
- Filing Date
- 2020-12-07
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2040-12-07
AI Technical Summary
Existing secondary battery electrode materials with an olivine crystal structure face challenges in achieving optimal electronic and ionic conductivity, leading to insufficient rate characteristics and cycle durability due to random carbon layer thickness variations and neglecting the one-dimensional high diffusion of carrier ions along the crystal axis b.
The active material features a carbon layer with a controlled thickness ratio on surfaces perpendicular and parallel to the crystal axis b, optimizing electronic conductivity and ion mobility, thereby enhancing rate characteristics and cycle durability.
The optimized carbon layer structure improves the rate characteristics and cycle durability of secondary batteries by balancing conductivity and ion diffusion, resulting in enhanced performance.
Smart Images

Figure 0007654979000003 
Figure 0007654979000004 
Figure 0007654979000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an active material for a secondary battery electrode and a secondary battery using the same. [Background technology]
[0002] In recent years, with the growing awareness of environmental issues, particularly global warming, the reduction of fossil fuel consumption has become an important issue. In particular, in the fields of power supply and transportation, which use large amounts of fossil fuels, the use of renewable energy as a source of supply and the electrification of power sources are being considered. In these fields, there is an increasing demand for power storage devices such as secondary batteries to level out power in the case of renewable energy and to store power sources in the case of electrification of power sources.
[0003] Lithium-ion secondary batteries, a type of secondary battery, have high energy density and excellent output characteristics, but if a malfunction occurs, the stored energy is released in a short time, and there is a risk of the battery catching fire or bursting into flames. Therefore, for lithium-ion secondary batteries, improving safety as well as improving output characteristics is an important issue.
[0004] It is well known that the safety of lithium-ion secondary batteries is largely determined by the positive electrode active material. The layered rock salt transition metal lithium oxide positive electrode active material, which is often used in large batteries for electric vehicles, etc., is a positive electrode active material that exhibits particularly high energy density, but it has safety issues such as accelerated deterioration due to changes in crystal structure accompanying oxygen release during charging and discharging, which may lead to the risk of smoke and fire depending on the usage conditions.
[0005] On the other hand, positive electrode active materials having an olivine crystal structure, such as lithium iron phosphate, are relatively stable and highly safe positive electrode materials even under high temperature conditions because oxygen is covalently bonded to phosphorus and does not easily release oxygen, but their electronic and ionic conductivity is known to be lower than that of layered rock salt-based transition metal lithium oxide positive electrode active materials. Therefore, the provision of a conductive carbon coating layer has been considered as a technology for improving the electronic and ionic conductivity of positive electrode active materials having an olivine crystal structure.
[0006] Regarding such a technique, there have been known a method for producing an electrode material having a core-shell structure in which an active material core is coated with carbon by heat-treating an electrode material precursor having a core-shell structure in which an active material core is coated with polyaniline in a reducing atmosphere at 300 to 900°C (see, for example, Patent Document 1); a lithium iron phosphate positive electrode material having primary particles of lithium iron phosphate with a conductive carbon coating layer, characterized in that the conductive carbon coating layer has a thick layer portion having a thickness of 2 nm or more and a thin layer portion having a thickness of less than 2 nm (see, for example, Patent Document 2); and an electrode material (see, for example, Patent Document 3) has been proposed which is composed of an aggregate formed by aggregating carbonaceous-coated electrode active material particles having a carbonaceous coating formed on the surface of the electrode active material particles at a coverage rate of 80% or more, the carbonaceous-coated electrode active material particles being composed of first carbonaceous-coated electrode active material particles on which a carbonaceous coating having a thickness of 0.1 nm or more and 3.0 nm or less and an average thickness of 1.0 nm or more and 2.0 nm or less is formed, and second carbonaceous-coated electrode active material particles on which a carbonaceous coating having a thickness of 1.0 nm or more and 10.0 nm or less and an average thickness of more than 2.0 nm and 7.0 nm or less is formed.
[0007] Incidentally, it is known that in an electrode active material having an olivine type crystal structure, carrier ions inside the material exhibit a one-dimensional high diffusion rate only in the direction of the crystal axis b (see, for example, Non-Patent Document 1). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2010-40357 A [Patent Document 2] JP 2012-216473 A [Patent Document 3] JP 2014-146513 A [Non-patent literature]
[0009] [Non-Patent Document 1] Gardiner, GR; Islam, MS Anti-Site Defects and Ion Migration in the LiFe0.5Mn0.5PO4 Mixed-Metal Cathode Material. Chem. Mater. 2010, 22 (3), 1242-1248. Summary of the Invention [Problem to be solved by the invention]
[0010] By forming a carbon layer on the surface of the secondary battery electrode active material having an olivine crystal structure, it is possible to improve the electronic conductivity and ionic conductivity, and improve the rate characteristics. In addition, in an electrode using such a secondary battery electrode active material, the area of direct contact between the electrolyte and the secondary battery electrode active material is reduced, thereby suppressing the dissolution of the secondary battery electrode active material into the electrolyte, and improving the cycle durability. From the viewpoint of improving the electronic conductivity and cycle durability, it is preferable that the carbon layer is thick.
[0011] On the other hand, from the viewpoint of facilitating the movement of carrier ions such as lithium in and out of the active material for secondary battery electrodes, the carbon layer is preferably thin. Although Patent Documents 1 to 3 disclose electrode active material particles having a carbon layer with varying thickness, the thickness of the carbon layer is changed randomly with respect to the crystal axis in all of them, and the above-mentioned phenomenon in which carrier ions in the electrode active material having an olivine crystal structure exhibit a one-dimensional high diffusion speed only in the direction of the crystal axis b is not utilized, and the effect of improving rate characteristics and cycle durability is insufficient.
[0012] In view of the above problems, an object of the present invention is to provide an active material for a secondary battery electrode that is excellent in rate characteristics and cycle durability. [Means for solving the problem]
[0013] In order to solve the above problems, the present invention mainly has the following configuration. The active material for a secondary battery electrode has an olivine crystal structure and a carbon layer on its surface, wherein the ratio of the average thickness of the carbon layer present on a surface perpendicular to a crystal axis b-axis to the average thickness of the carbon layer present on a surface not perpendicular to the b-axis is 0.30 or more and 0.80 or less. Effect of the Invention
[0014] By using the secondary battery electrode active material of the present invention, a secondary battery having excellent rate characteristics and cycle durability can be obtained. [Brief description of the drawings]
[0015] [Figure 1] 3A is a transmission electron microscope image of the secondary battery electrode active material of the present invention prepared in Example 2, and FIG. 3B is a Fourier transform image thereof. [Diagram 2] 1A is a transmission electron microscope image of a conventional secondary battery electrode active material prepared in Comparative Example 2, and FIG. 1B is a Fourier transform image thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The active material for secondary battery electrodes having an olivine crystal structure of the present invention (hereinafter sometimes simply referred to as "olivine active material") is characterized in that it has a carbon layer on its surface, and the ratio of the average thickness of the carbon layer present on a surface perpendicular to the crystal axis b-axis to the average thickness of the carbon layer present on a surface not perpendicular to the b-axis is 0.30 or more and 0.80 or less. As described above, by forming a carbon layer on the surface of the active material for secondary battery electrodes having an olivine crystal structure, it is possible to improve the rate characteristics and cycle durability. Furthermore, in the present invention, due to the crystallographic characteristics of the olivine-type active material, the carrier ions of the electrode, such as lithium and sodium (in this specification, the carrier ions refer to ions that enter and leave the active material during charging and discharging) show a one-dimensional high diffusion coefficient only in the direction of the crystal axis b-axis inside the olivine-type active material, and in order to improve the rate characteristics by reducing the thickness of the carbon layer in the direction of the crystal axis b-axis and promoting the entry and exit of the carrier ions into and out of the olivine-type active material, while in other directions, the carbon layer is made thicker and the cycle durability is improved, so the numerical range of the ratio of the average thickness of the carbon layer present on the plane perpendicular to the crystal axis b-axis to the average thickness of the carbon layer present on the plane not perpendicular to the b-axis is limited. The olivine-type active material of the present invention will be described below.
[0017] In the present invention, the olivine type active material is not particularly limited as long as it has an olivine type crystal structure, but it is preferable that it has a chemical composition represented by the general formula ABXO4 (A and B each independently represent one or more metal elements, and X represents any one or more elements other than metal elements). A is preferably an alkali metal, B is preferably a transition metal, and X is preferably silicon, phosphorus, or the like. Examples of chemical compositions represented by the general formula ABXO4 include LiFePO4, LiMnPO4, LiFe 1-x Mn xExamples include PO4 (0 < x < 1), LiCoPO4, LiNiPO4, NaFePO4, NaMnPO4, NaCoPO4, NaNiPO4, LiFeSiO4, NaFeSiO4, etc. Two or more of these may be contained. Among these, lithium generally tends to exhibit a high diffusion coefficient, so it is preferable to use lithium as the A site, and the rate characteristics can be further improved. Among olivine-type active materials, lithium iron manganese phosphate tends to have low electron conductivity and lithium ion conductivity, and the effect of the carbon layer in the present invention can be more significantly exhibited. For example, as described later, in Example 5 using lithium iron phosphate and Comparative Example 4, the energy density ratio is improved by 0.06. In Example 1 using lithium iron manganese phosphate and Comparative Example 1, the energy density ratio is improved by 0.16, and the effect of the carbon layer in the present invention is more significantly exhibited.
[0018] The olivine-type active material may have a structure with a different chemical composition (for example, a core-shell structure) inside the primary or higher-order particles. Further, the olivine-type active material may contain a doping element.
[0019] The olivine-type active material of the present invention has a carbon layer on its surface. The carbon layer only needs to cover at least a part of the surface of the olivine-type active material, and it is preferably to cover 80% or more of the surface area. Further, the carbon layer may have a functional group such as a carbonyl group or a hydroxyl group on its surface. From the viewpoint of further improving the electron conductivity and the rate characteristics, the content of the carbon layer in the olivine-type active material is preferably 1% by weight or more. On the other hand, from the viewpoint of suppressing the side reaction between the carbon layer and the olivine-type active material and further improving the cycle resistance, it is preferably 6% by weight or less.
[0020] Here, the content of the carbon layer in the olivine-type active material can be measured, for example, using a carbon-sulfur simultaneous quantitative analyzer EMIA-920V (manufactured by Horiba, Ltd.). The content of the carbon layer can be adjusted to a desired range, for example, by adjusting the addition amount of the carbon source added in the manufacturing method of the olivine-type active material described later.
[0021] In the olivine-type active material of the present invention, the ratio of the average thickness of the carbon layer present on the surface perpendicular to the crystal axis b-axis to the average thickness of the carbon layer present on the surface not perpendicular to the b-axis (average thickness of the carbon layer on the perpendicular surface / average thickness of the carbon layer on the non-perpendicular surface) is 0.30 or more and 0.80 or less. If the value of such a ratio is smaller than 0.30, the carbon layer on the surface perpendicular to the crystal axis b-axis becomes too thin, or the carbon layer on the surface not perpendicular to the crystal axis b-axis becomes too thick. In the former case, it is difficult to obtain the effect of improving the electronic conductivity by the carbon layer, and in the latter case, the weight ratio of the carbon layer in the olivine-type active material becomes too large, and in either case, the rate characteristics of the secondary battery are deteriorated. On the other hand, if the value of such a ratio is larger than 0.80, the carbon layer on the surface perpendicular to the crystal axis b-axis becomes too thick, or the carbon layer on the surface not perpendicular to the crystal axis b-axis becomes too thin. In the former case, it is difficult to obtain the effect of promoting the ingress and egress of carrier ions in and out of the olivine-type active material in the b-axis direction, and the rate characteristics of the secondary battery are deteriorated. In the latter case, it is difficult to obtain the effect of improving the cycle durability by the carbon layer, and the cycle durability of the secondary battery decreases.
[0022] The average thickness of the carbon layer on the surface perpendicular to the crystal axis b is preferably 0.6 nm or more, and preferably 2.0 nm or less, from the viewpoint of further improving the rate characteristics of the secondary battery. In the olivine-type active material of the present invention, when the surface of the olivine-type active material particle is regarded as a polyhedron, the thickness of the carbon layer in the same surface is preferably uniform, and the electric field applied to the olivine-type active material surface in the electrode reaction accompanying the charge and discharge of the secondary battery becomes uniform, thereby further improving the cycle durability. In particular, the thickness of the carbon layer on the surface perpendicular to the crystal axis b, where the thickness of the carbon layer is small, is preferably uniform, and the standard deviation of the thickness of the carbon layer on the surface perpendicular to the crystal axis b is preferably 0.3 nm or less.
[0023] Here, the average thickness of the carbon layer on the surface of the olivine-type active material on different crystal planes can be measured using a transmission electron microscope. Specifically, a multi-wave interference image of the olivine-type active material is measured under conditions of an acceleration voltage of 300 kV and a magnification of 2,000,000 times. The thickness of the carbon layer is measured at 20 or more measurement points evenly selected on the outer periphery of the particles of the olivine-type active material. In addition, the obtained lattice image is subjected to a Fourier transform, the distance from the origin to the bright point is measured, and the corresponding d value is calculated, thereby obtaining information on the crystal orientation. At each measurement point where the thickness of the carbon layer was measured, the crystal orientation perpendicular to the surface of the particle is calculated. If the angle between the crystal orientation perpendicular to the surface of the particle and the crystal axis b is 20 degrees or less, the corresponding measurement point is deemed to exist on a plane perpendicular to the crystal axis b. If the angle is greater than 20 degrees, the measurement point is deemed not to exist on a plane perpendicular to the crystal axis b. This process is performed for all measurement points, and the average thickness and standard deviation can be calculated for each of the carbon layers present on the plane perpendicular to the crystal axis b and the carbon layers present on the plane not perpendicular to the crystal axis b. The above-mentioned ratio value can be calculated from the obtained average thickness.
[0024] As a method for adjusting the average thickness ratio and standard deviation of the carbon layers to fall within the above ranges, for example, there can be mentioned a method for obtaining an olivine type active material by the manufacturing method described below.
[0025] The crystallite diameter of the olivine type active material of the present invention is preferably 60 nm or less. Olivine type active materials generally have low electronic and ionic conductivity, and therefore tend to have a large voltage drop under conditions of large charge / discharge currents. By setting the crystallite diameter to 60 nm or less, the diffusion distance of electrons and carrier ions within the crystallites is shortened, and the rate characteristics can be further improved. Since the specific surface area of active material particles having a small crystallite diameter is large, the effect of the average thickness ratio of the carbon layer in the present invention can be more significantly achieved.
[0026] Here, the crystallite size of the olivine-type active material can be calculated by performing powder X-ray diffraction measurement on a powder sample of the olivine-type active material under conditions of a diffraction angle 2θ of 10 degrees or more and 70 degrees or less, and performing Rietveld analysis on the obtained diffraction pattern. The olivine-type active material of the present invention may be measured directly, or in the case of a secondary battery described later, the olivine-type active material obtained by grinding an electrode mixture peeled off from a secondary battery electrode may be measured. The crystallite size of the olivine-type active material can be adjusted to a desired range, for example, by adjusting the mixing ratio of water and an organic solvent used as a solvent, the total amount of the solvent relative to the raw materials, the synthesis temperature, the firing temperature, etc. in the manufacturing method of the olivine-type active material described later.
[0027] Among the olivine-type active materials in the present invention, the crystallinity and particle shape of the lithium manganese iron phosphate can be determined by the ratio I of the peak intensity at 20° to the peak intensity at 29° obtained by X-ray diffraction. 20 / I 29 , the ratio of the peak intensity at 35° to the peak intensity at 29° I 35 / I 29 It can be evaluated by: 20 / I 29 When the ratio is 0.88 or more and 1.05 or less, it means that the lithium manganese iron phosphate is not highly oriented in the b-axis direction, and the particle shape is closer to a sphere than a plate shape. By making the particles closer to a spherical shape, the distortion of the crystal lattice caused by the insertion and removal of lithium ions during charging and discharging can be alleviated, and the rate characteristic and cycle durability can be further improved. In addition, I 35 / I 29 When the ratio is 1.05 or more and 1.20 or less, the crystal orientation of the lithium manganese iron phosphate is further decreased, the crystal orientation is more uniform, and the particle shape is closer to a sphere. Therefore, the distortion of the crystal lattice caused by the insertion and removal of carrier ions during charging and discharging can be alleviated, and the rate characteristic and cycle durability can be further improved. 20 / I 29 and I 35 / I 29 As a method for adjusting the content to the above range, for example, a method for obtaining lithium manganese iron phosphate by the production method described later can be mentioned.
[0028] Next, a method for producing the olivine type active material of the present invention will be described. The olivine type active material of the present invention can be obtained by any method such as a solid phase method or a liquid phase method. The liquid phase method is preferred because it is easy to adjust the crystallite size to the above-mentioned preferred range. In addition to water, it is also suitable to use an organic solvent in the liquid phase to refine the crystallites to nanoparticles, and examples of the solvent include alcohol solvents such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 2-propanol, 1,3-propanediol, and 1,4-butanediol, and dimethyl sulfoxide. Two or more of these may be used. In the synthesis process, pressure may be applied to increase the crystallinity of the particles. The chemical composition of the olivine type active material can be adjusted to a desired range by the charging ratio of the raw materials. In addition, in the synthesis of lithium manganese iron phosphate by the liquid phase method, it is preferable to add a solution containing the remaining raw materials while stirring a part of the raw materials at high speed, and heat the solution to the synthesis temperature without applying pressure while maintaining the high speed stirring state, and the peak intensity ratio I obtained by X-ray diffraction of lithium manganese iron phosphate is 1.0 to 1.0 times the ratio of the peak intensity I 20 / I 29 and I 35 / I 29 can be easily adjusted to fall within the above-mentioned preferred range.
[0029] When the primary particles of the olivine-type active material are obtained by the liquid phase method, the crystallite size can be adjusted to a desired range by, for example, the mixing ratio of water and organic solvent in the solvent, the concentration of the synthesis solution, the synthesis temperature, the charging ratio of the raw materials, etc. Typically, in order to increase the crystallite size, it is effective to increase the proportion of water in the solvent, to increase the concentration of the synthesis solution, to increase the synthesis temperature, etc.
[0030] As a carbon coating method for forming a carbon layer on an olivine type active material obtained by a liquid phase method, a method of mixing a powder consisting of primary particles and / or secondary particles of an olivine type active material or a slurry containing these with a carbon source and then baking under an inert gas atmosphere is preferred. Examples of carbon sources include sugars such as glucose, sucrose, trehalose, maltose, dextrin hydrate, and cyclodextrin, organic acids such as citric acid, malic acid, succinic acid, fumaric acid, and maleic acid, organic polymers such as polyaniline, polyacrylonitrile, polyvinyl alcohol, and polyvinylpyrrolidone, and crude oils such as coal tar, pitch, and asphalt. Two or more of these may be used. Among these, when only sugars or organic polymers are used as carbon sources, the standard deviation of the thickness of the carbon layer can be easily adjusted to the above-mentioned preferred range.
[0031] As a method for mixing the olivine type active material with the carbon source, it is preferable to dissolve or disperse the carbon source and the olivine type active material in a medium such as water, ethanol, acetonitrile, N-methylpyrrolidone, or dimethyl sulfoxide, and mix and disperse them using a mixing device such as a disper, jet mill, high-shear mixer, or ultrasonic homogenizer.
[0032] In order to set the average thickness ratio of the carbon layer relative to the crystal axis b-axis direction in the above-mentioned range, it is preferable to instantly dry the slurry containing the olivine-type active material and the carbon source prior to firing to obtain a precursor of the olivine-type active material in which the olivine-type active material and the carbon source are intimately mixed. Specifically, it is preferable to dry the slurry using a spray dryer.
[0033] Examples of the inert gas used during firing include nitrogen and argon. In order to remove the gas generated from the mixture of the olivine type active material and the carbon source during firing, it is preferable to flow the inert gas. The firing temperature is preferably 500°C or higher and 1000°C or lower, and the firing time is preferably 30 minutes or longer and 24 hours or shorter.
[0034] In order to set the average thickness ratio of the carbon layer to the crystal axis b-axis direction in the above-mentioned range, it is preferable to combine multiple compounds with different melting points as carbon sources, perform pre-firing at a temperature between the melting point of the compound with the lower melting point and the melting point of the compound with the higher melting point for 1 hour to 24 hours prior to the above-mentioned firing, and then perform firing under the above-mentioned conditions. By adjusting the mixing ratio of the carbon sources with different melting points, it is possible to adjust the average thickness ratio of the carbon layer to the crystal axis b-axis direction. In this case, it is preferable to set the amount of the compound with the highest melting point to 0.50 times or more and 5.0 times or less of the total amount of the compounds with a lower melting point than that compound.
[0035] When the primary particle diameter of the olivine type active material is smaller than 1 μm, the active material is preferably handled as secondary particles formed by agglomeration of the primary particles, and the secondary particle diameter is preferably 3 μm or more from the viewpoint of the handleability of the paste in the manufacturing method of a secondary battery electrode described later. On the other hand, the secondary particle diameter of the olivine type active material is preferably 40 μm or less from the viewpoint of the thickness of the mixture layer described later.
[0036] The secondary particle diameter of the olivine-type active material refers to the arithmetic mean value of the particle diameter of the secondary particles, and can be measured using a scanning electron microscope. Specifically, the electrode is observed at a magnification of 3,000 times using a scanning electron microscope, and the secondary particle diameter of 100 randomly selected secondary particles is measured. The secondary particle diameter of the olivine-type active material can be obtained by calculating the number average value. If less than 100 secondary particles are observed in one observation field, observation is performed at another location of the sample until the cumulative number of observed secondary particles reaches 100. In addition, the secondary particle diameter of the secondary particles of the olivine-type active material used as a raw material in the manufacture of the electrode may be measured using a scanning electron microscope in the same manner.
[0037] As a method for producing the secondary particles of an olivine type active material, from the viewpoint of narrowing the particle size distribution of the secondary particles as much as possible, a method of drying and granulating a dispersion containing the primary particles of an olivine type active material using a spray dryer is preferable. The secondary particle size of the olivine type active material can be easily adjusted to a desired range, for example, by changing the weight concentration of the aqueous dispersion of the olivine type active material as the raw material in the above-mentioned method for producing an olivine type active material.
[0038] The olivine type active material particles of the present invention are suitable for use in secondary battery electrodes. The secondary battery electrode of the present invention preferably has a mixture layer containing the olivine type active material of the present invention and additives such as binders and conductive assistants on a current collector such as aluminum foil, copper foil, stainless steel foil, or platinum foil. In addition to the olivine type active material of the present invention, other active materials such as active materials having a layered oxide type crystal structure and active materials having a spinel type crystal structure may also be contained.
[0039] Examples of the binder include polyvinylidene fluoride, styrene-butadiene rubber, etc. Two or more of these may be contained.
[0040] The content of the binder in the electrode mixture layer is preferably 0.3% by weight or more and 10% by weight or less. By making the content of the binder 0.3% by weight or more, the shape of the coating film can be easily maintained when the coating film is formed due to the binding effect of the binder. On the other hand, by making the content of the binder 10% by weight or less, an increase in the resistance in the electrode can be suppressed.
[0041] Examples of the conductive assistant include acetylene black, ketjen black, carbon fiber, carbon nanotube, graphene, reduced graphene oxide, etc. Two or more of these may be contained.
[0042] The content of the conductive assistant in the mixture layer is preferably 0.3% by weight or more and 10% by weight or less. By making the content of the conductive assistant 0.3% by weight or more, the conductivity of the electrode can be improved and the electronic resistance can be reduced. On the other hand, by making the content of the conductive assistant 10% by weight or less, the inhibition of the movement of carrier ions in the battery by the conductive assistant can be suppressed, and the ion conductivity can be further improved.
[0043] In order to increase the energy density of the secondary battery, it is preferable that the electrode mixture layer contains an olivine type active material at as high a ratio as possible, and the total content of the olivine type active material and other active materials in the electrode mixture layer is preferably 80% by weight or more, and more preferably 85% by weight or more.
[0044] The thickness of the electrode mixture layer is preferably 10 μm or more and 200 μm or less. By making the thickness of the mixture layer 10 μm or more, the ratio of the current collector in the electrode can be reduced, and the energy density can be further improved. On the other hand, by making the thickness of the mixture layer 200 μm or less, the charge / discharge reaction can be rapidly progressed throughout the mixture layer, and the high-speed charge / discharge characteristics can be improved.
[0045] The secondary battery electrode can be obtained, for example, by applying a paste in which the above-mentioned olivine-type active material secondary particles are dispersed in a dispersion medium onto a current collector, drying, and pressing to form a mixture layer. As a method for producing the paste, it is preferable to mix and knead the above-mentioned olivine-type active material secondary particles, and further additives such as a conductive assistant, a binder, and a dispersion medium such as N-methylpyrrolidinone as necessary, and add water or a dispersion medium such as N-methylpyrrolidinone to adjust the viscosity. The solid content concentration of the paste can be appropriately selected depending on the application method. From the viewpoint of making the coating film thickness uniform, it is preferable to be 30% by weight or more and 80% by weight or less. Each material of the paste may be mixed at once, or in order to uniformly disperse each material in the paste, it may be added and mixed in order while repeating kneading. As a kneading device for the slurry, a planetary mixer or a thin film swirl type high-speed mixer is preferable in terms of being able to knead uniformly.
[0046] The secondary battery of the present invention preferably has a counter electrode, a separator, and an electrolyte in addition to the above-mentioned electrodes. The shape of the battery may be, for example, a coin type, a square type, a wound type, a laminate type, or the like, and may be appropriately selected according to the purpose of use. Materials constituting the counter electrode may be, for example, graphite, lithium titanate, silicon oxide, lithium cobalt oxide, or the like. The separator and electrolyte may also be appropriately selected and used.
[0047] The secondary battery of the present invention can be obtained, for example, by laminating the above-mentioned secondary battery electrode with a counter electrode via a separator in a dry environment with a dew point of −50° C. or lower, and adding an electrolyte solution. EXAMPLES
[0048] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. First, the evaluation methods used in the examples will be described.
[0049] [Measurement A] Carbon layer average thickness and standard deviation A multi-wave interference image was measured for the powder samples made of the olivine-type active material secondary particles obtained in each Example and Comparative Example using a transmission electron microscope under conditions of an acceleration voltage of 300 kV and a magnification of 2,000,000 times. To explain using the figures, in FIG. 1(a), the thickness of the carbon layer was measured for 21 selected points selected approximately evenly on the periphery of the observed primary particle. In addition, at each measurement point where the thickness of the carbon layer was measured, in FIG. 1(b), which is a two-dimensional Fourier transform of the obtained lattice image, the distance from the origin to the bright point was measured and the corresponding d value was calculated (0.630 nm and 0.534 nm in FIG. 1(b)), and the crystal orientation was assigned by applying the closest interplanar spacing, and the crystal orientation perpendicular to the surface of the particle was calculated.
[0050] In Figure 1(b), 0.630 nm corresponds to (010) and 0.534 nm corresponds to (100). The crystal axis b-axis is parallel to (010).
[0051] In this specification, the index in parentheses as the crystal orientation indicates a plane in normal crystallography, but in this specification, it indicates the direction of the normal to the plane. The direction of the normal to the plane can be expressed by the fundamental translation vectors k1, k2, and k3 of the reciprocal lattice (arrows omitted) corresponding to the crystal lattice, as shown in the following formula.
[0052]
number
[0053] (where x1, x2, x3 (arrow notation omitted) represent fundamental translation vectors parallel to the a-axis, b-axis, and c-axis of the crystal lattice, respectively.) When the angle between the crystal orientation perpendicular to the particle surface and the crystal axis b is 20 degrees or less, the corresponding measurement point is considered to be on a plane perpendicular to the crystal axis b, and when the angle is greater than 20 degrees, the measurement point is considered not to be on a plane perpendicular to the crystal axis b. In Figure 1(b), the angle between (010) and the b axis is 0 degrees, and the angle between (100) and the b axis is 90 degrees.
[0054] In addition, if there was only one point or less on the observed primary particle where the angle with the crystal axis b-axis was 20 degrees or less, the b-axis was considered to be perpendicular to the observation surface of the microscope image, and a different primary particle was observed.
[0055] In this manner, the average thickness X of the carbon layer present on the surface perpendicular to the crystal axis b, the average thickness Y of the carbon layer present on the surface not perpendicular to the crystal axis b, and the standard deviation of the thickness of the carbon layer present on the surface perpendicular to the crystal axis b were each calculated.
[0056] [Measurement B] Crystallite size and X-ray diffraction peak intensity ratio Powder samples consisting of secondary particles of olivine-type active material obtained in each Example and Comparative Example were subjected to powder X-ray diffraction measurement under the condition of a diffraction angle 2θ of 10 degrees or more and 70 degrees or less, using an X-ray diffractometer D8 ADVANCE manufactured by Bruker AXS Inc. Based on the obtained diffraction pattern, Rietveld analysis was performed using analysis software TOPAS manufactured by Bruker AXS Inc., and the crystallite diameter of the olivine-type active material was calculated.
[0057] The analysis was performed assuming an olivine-type crystal structure as the starting structure, and the GOF (=(R wp / R exp ) 2 When the I value was less than 4.0, the active material was deemed to have an olivine crystal structure. The peak intensity ratios were calculated by removing the background (factor 1.77) and reading the peak intensities using DIFFRAC.EVA, a powder X-ray diffraction analysis software manufactured by Bruker AXS Co., Ltd. The peak intensities at 20° and 35° divided by the peak intensity at 29° were calculated as I 20 / I 29 , I 35 / I 29 It was decided.
[0058] [Measurement C] Rate characteristics of secondary batteries A 2032-type coin battery was produced by cutting the electrode plate obtained in each Example and Comparative Example to a diameter of 15.9 mm to form a positive electrode, cutting a lithium foil to a diameter of 16.1 mm and a thickness of 0.2 mm to form a negative electrode, using "Setira" (registered trademark) as a separator, and using ethylene carbonate:diethyl carbonate = 3:7 (volume ratio) containing LiPF6 at a concentration of 1 M as an electrolyte.
[0059] The fabricated 2032-type coin battery was charged and discharged twice at a 0.1C rate, followed by two cycles at a 3C rate, with a cutoff voltage of 2.5 V and a maximum charging voltage of 4.3 V. For each charge and discharge rate, the discharge energy was measured from the second discharge, and the rate characteristics were evaluated by calculating the ratio of the energy at the 3C rate divided by the energy at the 0.1C rate.
[0060] [Measurement D] Cycle durability of secondary batteries A laminated cell with a capacity of 1 Ah was produced using the electrode plates obtained in each of the Examples and Comparative Examples, a commercially available carbon-based negative electrode (negative electrode active material: artificial graphite MAG manufactured by Hitachi Chemical Co., Ltd.) as the negative electrode, "Setira" (registered trademark) as the separator, and ethylene carbonate:diethyl carbonate = 3:7 (volume ratio) containing 1M LiPF6 as the electrolyte. The number of layers was 7 layers for the positive electrode (size: 70 mm x 40 mm) and 8 layers for the negative electrode (size: 74 mm x 44 mm), and the capacity ratio (NP ratio) of the opposing positive and negative electrodes was 1.05.
[0061] The laminated cell thus fabricated was charged and discharged three times at a rate of 0.1C in an environment of 25°C, and then subjected to a cycle test in which it was repeatedly charged and discharged at a rate of 1C in an environment of 55°C. The energy density in the first discharge test in an environment of 55°C was taken as 100%, and the number of cycles until the energy density fell below 80% was measured to evaluate the cycle durability.
[0062] [Example 1] (Step 1: Preparation of secondary particles of olivine type active material) After dissolving 60 mmol of lithium hydroxide monohydrate in 16 g of pure water, 104 g of diethylene glycol was added to prepare a lithium hydroxide / diethylene glycol aqueous solution. The obtained lithium hydroxide / diethylene glycol aqueous solution was stirred at 2000 rpm using a homodisper (Homodisper 2.5 type manufactured by Primix Corporation), and an aqueous solution obtained by dissolving 20 mmol of phosphoric acid (85% aqueous solution), 16 mmol of manganese (II) sulfate monohydrate, and 4 mmol of iron (II) sulfate heptahydrate in 10 g of pure water was added to obtain an olivine-type structure lithium manganese iron phosphate nanoparticle precursor. The obtained precursor solution was heated to 110°C and held for 2 hours to obtain lithium manganese iron phosphate as a solid content. Pure water was added to the obtained particles, and the particles were washed by repeatedly removing the solvent using a centrifuge. The synthesis was repeated until the amount of lithium manganese iron phosphate obtained by washing reached 10 g.
[0063] 1.0 g of glucose (melting point 146°C) and 0.75 g of polyvinyl alcohol (melting point 300°C) as carbon sources and 40 g of pure water were added to 10 g of the obtained lithium manganese iron phosphate, mixed, and granulated using a spray dryer (Yamato Scientific ADL-311-A) under conditions of a nozzle diameter of 400 μm, a drying temperature of 150°C, and an atomizing pressure of 0.2 MPa. The obtained granules were pre-calcined in a calciner at 175°C for 1 hour, and then calcined at 700°C for 1 hour in a nitrogen atmosphere to obtain a powder sample consisting of secondary particles of lithium manganese iron phosphate.
[0064] (Step 2: Preparation of electrode plate) Acetylene black (Li-400 manufactured by Denka Co., Ltd.) and binder (Kureha KF Polymer Co., Ltd. L#9305) were mixed, and the secondary particles of lithium iron manganese phosphate obtained by the above method were added and kneaded in a mortar. At that time, the weight ratio of each material contained was adjusted to 90:5:5, i.e., secondary particles of lithium iron manganese phosphate: acetylene black: binder. Then, N-methylpyrrolidinone was added to adjust the solid content to 48% by weight, and a slurry-like electrode paste was obtained. N-methylpyrrolidinone was added until the obtained paste had fluidity, and the paste was treated for 30 seconds under stirring conditions of 40 m / sec using a thin film rotating high-speed mixer (Primix Corporation's "Filmix" (registered trademark) 40-L type).
[0065] The obtained electrode paste was applied to an aluminum foil (thickness 18 μm) using a doctor blade (300 μm), dried at 80° C. for 30 minutes, and then pressed to prepare an electrode plate.
[0066] [Example 2] Secondary particles of lithium manganese iron phosphate and an electrode plate were produced in the same manner as in Example 1, except that the amount of glucose used in step 1 was 1.50 g and the amount of polyvinyl alcohol used was 1.10 g. Figure 1(a) shows a transmission electron microscope image of the obtained secondary particles of lithium manganese iron phosphate, and Figure 1(b) shows its Fourier transform image. In Figure 1(a), the reference symbol 1 indicates the thickness of the carbon layer at each measurement point.
[0067] [Example 3] Lithium manganese iron phosphate secondary particles and an electrode plate were prepared in the same manner as in Example 1, except that in step 1, a reduced-pressure heavy oil stock solution having a viscosity of 600 mPa sec at 20°C (measured with a Brookfield viscometer at a rotation speed of 6 rpm) was used instead of glucose.
[0068] [Example 4] Secondary particles of lithium iron manganese phosphate and an electrode plate were produced in the same manner as in Example 1, except that the amount of diethylene glycol added in step 1 was 60 g.
[0069] [Example 5] Secondary particles of olivine-type active material and an electrode plate were prepared in the same manner as in Example 1, except that the amount of iron (II) sulfate heptahydrate added in step 1 was 20 mmol, and no manganese (II) sulfate monohydrate was added.
[0070] [Example 6] 200g of dimethyl sulfoxide and 390mmol of lithium hydroxide monohydrate were added to 150g of pure water. 120mmol of phosphoric acid was further added to the obtained solution using an 85wt% phosphoric acid aqueous solution, 84mmol of manganese (II) sulfate monohydrate, and 36mmol of iron (II) sulfate heptahydrate were added. The obtained solution was transferred to an autoclave and heated and held for 4 hours so that the temperature inside the container was maintained at 150°C. After heating, the supernatant of the solution was discarded, and lithium manganese iron phosphate was obtained as a precipitate. The obtained lithium manganese iron phosphate was dispersed in pure water, and then the operation of removing the supernatant by centrifugation was repeated five times to perform washing. A powder sample consisting of lithium manganese iron phosphate secondary particles was obtained from 10g of the obtained lithium manganese iron phosphate in the same manner as in Example 1. Thereafter, olivine type active material secondary particles and an electrode plate were produced in the same manner as in Example 1.
[0071] [Comparative Example 1] Secondary particles of lithium manganese iron phosphate and an electrode plate were produced in the same manner as in Example 1, except that the amount of glucose added in step 1 was 0.25 g and the amount of polyvinyl alcohol added was 1.5 g.
[0072] [Comparative Example 2] A granule was obtained in the same manner as in Example 1, except that the amount of glucose added in step 1 was 1.75 g and no polyvinyl alcohol was added. The obtained granule was sintered in a sintering furnace at 700°C for 1 hour under a nitrogen atmosphere to obtain a powder sample consisting of secondary particles of lithium iron manganese phosphate. Thereafter, an electrode plate was produced in the same manner as in step 2 of Example 1. Figure 2(a) shows a transmission electron microscope image of the obtained lithium iron manganese phosphate nanoparticle granule, and Figure 2(b) shows its Fourier transform image (b).
[0073] [Comparative Example 3] 200g of dimethyl sulfoxide and 390mmol of lithium hydroxide monohydrate were added to 150g of pure water. 120mmol of phosphoric acid was further added to the obtained solution using 85wt% phosphoric acid aqueous solution, 84mmol of manganese (II) sulfate monohydrate, and 36mmol of iron (II) sulfate heptahydrate were added. The obtained solution was transferred to an autoclave and heated for 4 hours so that the temperature inside the container was maintained at 150°C. After heating, the supernatant of the solution was discarded, and lithium manganese iron phosphate was obtained as a precipitate. The obtained lithium manganese iron phosphate was dispersed in pure water, and the operation of removing the supernatant by centrifugation was repeated five times to wash it. 10g of the obtained lithium manganese iron phosphate was added with 10g of pure water and 0.75g of glucose and stirred to obtain a lithium manganese iron phosphate dispersion, and then granulated using a spray dryer (ADL-311-A manufactured by Yamato Scientific) with a nozzle diameter of 400μm, a drying temperature of 150°C, and an atomizing pressure of 0.2MPa. The obtained granulated particles were sintered in a sintering furnace at 700° C. for 1 hour in a nitrogen atmosphere to obtain a powder sample made of secondary particles of lithium iron manganese phosphate. Then, an electrode plate was produced in the same manner as in step 2 of Example 1.
[0074] [Comparative Example 4] Olivine-type active material secondary particles and an electrode plate were prepared in the same manner as in Comparative Example 3, except that manganese (II) sulfate monohydrate was not added and the amount of iron (II) sulfate heptahydrate added was 120 mmol.
[0075] [Comparative Example 5] 200g of dimethyl sulfoxide and 390mmol of lithium hydroxide monohydrate were added to 150g of pure water. 120mmol of phosphoric acid was further added to the obtained solution using 85wt% phosphoric acid aqueous solution, 84mmol of manganese(II) sulfate monohydrate, and 36mmol of iron(II) sulfate heptahydrate were added. The obtained solution was transferred to an autoclave and heated and held for 4 hours so that the inside of the container was maintained at 150°C. After heating, the supernatant of the solution was discarded, and lithium manganese iron phosphate was obtained as a precipitate. The obtained lithium manganese iron phosphate was dispersed in pure water, and the operation of removing the supernatant by centrifugation was repeated five times for washing.
[0076] To 10 g of the obtained lithium manganese iron phosphate, a reduced pressure heavy oil stock solution having a viscosity of 600 mPa sec at 20°C (measured with a Brookfield viscometer at a rotation speed of 6 rpm) was added in an amount of 4.0% by weight relative to the weight of the lithium manganese iron phosphate, and the mixture was further precisely mixed using a jet mill (manufactured by Sugino Machine), and then calcined at 700°C for 3 hours.
[0077] [Comparative Example 6] A granule was obtained in the same manner as in Example 1, except that the amount of glucose added in step 1 was 2.50 g and no polyvinyl alcohol was added. The obtained granule was fired in a firing furnace at 700°C for 1 hour under a nitrogen atmosphere to obtain a powder sample consisting of secondary particles of lithium iron manganese phosphate. This powder sample and a powder sample obtained in the same manner as in Comparative Example 2 were mixed in a mortar at a weight ratio of 1:1 to obtain an olivine type active material powder. Thereafter, an electrode plate was produced in the same manner as in step 2 of Example 1.
[0078] The evaluation results of each of the examples and comparative examples are shown in Table 1.
[0079] [Table 1] [Explanation of symbols]
[0080] 1 Thickness of the carbon layer at each measurement point 2. Origin 3 bright spots 4 Distance from the origin to the bright spot
Claims
1. The active material for a secondary battery electrode has an olivine crystal structure and a carbon layer on a surface thereof, wherein the ratio of the average thickness of the carbon layer present on a surface perpendicular to a crystal axis b-axis to the average thickness of the carbon layer present on a surface not perpendicular to the b-axis is 0.30 or more and 0.80 or less, and the average thickness of the carbon layer present on a surface perpendicular to the crystal axis b-axis is 0.6 nm or more and 2.24 nm or less.
2. 2. The secondary battery electrode active material according to claim 1, wherein the carbon layer existing on a plane perpendicular to the crystal axis b has an average thickness of 2.0 nm or less.
3. 3. The secondary battery electrode active material according to claim 1, wherein the standard deviation of the thickness of the carbon layer present on a plane perpendicular to the crystal axis b is 0.3 nm or less.
4. 4. The secondary battery electrode active material according to claim 1, wherein the crystallite size is 60 nm or less.
5. General formula ABXO 4 (A and B each independently represent one or more metal elements, and X represents any one or more elements other than metal elements), wherein lithium occupies at least a part of the A site of an olivine-type crystal structure represented by the formula:
6. 6. The secondary battery electrode active material according to claim 1, which is lithium manganese iron phosphate.
7. Ratio I of the peak intensity at 20° to the peak intensity at 29° obtained by X-ray diffraction 20 / I 29 is 0.88 or more and 1.05 or less, and the ratio I 35 / I 29 The secondary battery electrode active material according to claim 6 , wherein the value of the σ is 1.05 or more and 1.20 or less.
8. A secondary battery comprising the active material for a secondary battery electrode according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for manufacturing electrode material precursor, and method for manufacturing electrode material using the same
JP2010040357A
Lithium secondary battery and positive electrode for lithium secondary battery
JP2011076820A
Iron lithium phosphate positive electrode material and manufacturing method of the same
JP2012216473A
Electrode material and electrode, and lithium ion battery
JP2014146513A
Electrode material for lithium ion secondary battery, method for manufacturing the same, electrode for lithium ion secondary battery and lithium ion secondary battery
JP2018163762A